EVALUASI MUTU KOPI ROBUSTA DI KECAMATAN KARE KABUPATEN MADIUN JAWA TIMUR - Choiroel Anam; Eny Muzayana; Rohmat Priya Atmaja; Didik Purnomo (Pro Food, 2020)
ABSTRACT Coffee is a leading commodity in Madiun Regency, East Java, the area of coffee plantations in 2018 is 1,432 Ha with an average productivity of 769.63 kg / ha /year. This study aims to provide information on the physical, chemical, and microbiological quality characteristics of rice coffee, roasted coffee beans and evaluate the primary processing procedures for Mugi Lestari Farmer Group's coffee in Kare Village, Kare District, Madiun Regency. Evaluation of the quality of coffee rice is based on general and specific quality equirements according to SNI 01-2907: 2008. Organoleptic and chemical analysis of rice coffee and roasted coffee beans was carried out to see the state (smell, taste), moisture content, ash content, ash alkalinity, caffeine content, sugar content (reducing), insoluble solids, metal contaminants (Pb and Cu). Assessment of the physical quality of coffee beans shows that the robusta rice coffee produced at Poktan Mugi Lestari has quality according to SNI 01-2907-2008, especially for the parameters of the presence of insects, moisture content, impurities, and no found odor/mold. Physical quality of roasted coffee beans from Poktan Mugi Lestari when compared to SNI standards has a normal condition, both in terms of smell, taste, and appearance. Chemical parameters of roasted coffee bean samples are also in accordance with the general requirements for roasted coffee (SNI 01-2983-1992). The number of bacteria and molds is less than the maximum limit set. Assessment of physical, chemical, and microbiological quality of packaged coffee powder has a value in accordance with the SNI quality requirements, both for caffeine content, the amount of mold, and bacteria (ALT value), and water content. The primary coffee processing process at Poktan Mugi Lestari has been able to produce rice coffee in accordance with SNI requirements. Keywords: coffee, robusta, quality, kare madiun ABSTRAK Kopi merupakan komoditas unggulan di Kabupaten madiun Jawa Timur, Luas areal perkebunan kopi tahun 2018 di Kabupaten Madiun 1.432 Ha dengan produktivitas rata rata 769,63 kg/ha/tahun. Penelitian ini bertujuan memberikan informasi karakteristik mutu fisik, kimiawi, dan mikrobiologis dari kopi beras, kopi biji sangrai dan mengevaluasi prosedur pengolahan primer kopi Kelompok Tani Mugi Lestari di desa Kare, Kecamatan Kare, Kab Madiun, agar dihasilkan produk dengan mutu yang baik. Evaluasi mutu kopi beras didasarkan pada syarat mutu umum dan khusus sesuai SNI 01-2907:2008. Analisa organoleptik dan kimiawi kopi beras dan kopi biji sangrai dilakukan untuk melihat keadaan (bau, rasa), kadar air, kadar abu, kealkalian abu, kadar kafein, kadar gula (pereduksi), padatan tak larut dalam air, cemaran logam (Pb dan Cu). Penilaian mutu fisik biji kopi diketahui bahwa kopi beras robusta yang dihasilkan di Poktan Mugi Lestari memiliki mutu sesuai dengan SNI 01-2907-2008, khususnya untuk parameter keberadaan serangga, nilai kadar air, pengotor, dan tidak ditemukannya bau busuk/kapang. Keadaan mutu fisik biji kopi sangrai dari Poktan Mugi Lestari jika dibandingan dengan SNI 01-2983-1992 memiliki keadaan yang normal, baik dalam hal bau, rasa, dan penampakan. Parameter kimiawi biji kopi sangrai dalam penelitian juga sesuai dengan syarat umum kopi sangrai (SNI 01-2983-1992). Jumlah bakteri dan kapang kurang dari batas maksimum yang ditetapkan. Penilaian mutu fisik, kimiawi, dan mikrobiologis bubuk kopi yang dikemas memiliki nilai sesuai dengan persyaratan mutu SNI, baik untuk kadar kafein, jumlah kapang, dan bakteri (nilai ALT), dan kadar air. Proses pengolahan primer kopi di Poktan Mugi Lestari sudah mampu menghasilkan kopi beras yang sesuai dengan persyaratan SNI. Kata kunci: Kopi, Robusta, Mutu, Kare Madiun